Green biosynthesis of silver nanoparticles using anthocyanins-rich extract from Euterpe edulis fruits (AnthocyanOx®): Assessment in vitro of antioxidant and antiglycation activities, and in silico anti-aging activity - Santos, Valter Henrique Marinho dos; Costa, Monique Maria de Oliveira [UNESP]; Granero, Filipe Oliveira [UNESP]; Figueiredo, Célia Cristina Malaguti [UNESP]; Santos, Hugo Henrique [UNESP]; Benevides, Paulo José Coelho; Nicolau-Junior, Nilson; Debiagi, Paulo Eduardo Amaral; Silva, Luciana Pereira [UNESP]; Silva, Regildo Márcio Gonçalves da [UNESP] (Elsevier, 2025)
The standardized plant extract rich in anthocyanins (approximately 15,000 ppm) extracted from E. edulis fruits (AnthocyanOx®) has demonstrated potential uses and applications for the development of new products in food, cosmetic, and pharmaceutical industries. Anthocyanins provide several health benefits, showing potential to prevent damage and diseases caused by oxidative stress, protein glycation, and premature aging. New formulations enhancing benefits of standardized extract have been developed and green synthesis of metallic nanoparticles have attracted great interest. Techniques such as UV-Visible spectroscopy, Dynamic Light Scattering (DLS), and Scanning Electron Microscopy (SEM) were conducted to characterize silver nanoparticles (AgNPs) synthesized using AnthocyanOx® aqueous extract (EeAE). Antioxidant activity was assessed through DPPH radical scavenging, Ferric Reducing Antioxidant Power (FRAP), ABTS radical scavenging, and Oxygen Radical Absorbance Capacity (ORAC). Molecular docking analyses were conducted to evaluate molecular interactions. The characterization demonstrated AgNPs formation. Antioxidant evaluations showed high antioxidant activity for both EeAE and AgNPs. In silico assays demonstrated that anthocyanins interacted with all enzymes evaluated. These results represent an important indicator for the development and discovery of new nanostructured formulations using standardized extracts rich in anthocyanins extracted from E. edulis for food, cosmetic, and pharmaceutical industries.
Keywords: Anthocyanins; Antiglycation activity; Antioxidant activity; Green synthesis; Silver nanoparticles